Productive generations and careers: what do (Y Gen) women want? - Lemos, Ana Heloísa Costa; Mello, Giselle Rohr; Guimarães, Mayara Farias (Revista de Administração da UFSM, 2014)
Despite the attention that Generation Y has received in recent times, studies that map the attitudes related to work of these individuals has devoted little attention to understanding the differences that gender can produce in the same generational group. However, we believe that gender differences should be better understood, because, according to the IBGE (2012), women represent 45.4% of the current Brazilian labor force. The growing importance of women in the labor market brings the challenge for organizations to attract and retain that portion of the workforce, whose demands are not necessarily equal those of men. The scarcity of studies on the expectations related to career of Gen Y women motivated the present work, which sought to understand the desires of young professionals with regard to the construction of their professional careers. To answer these questions we carried out a qualitative research, interviewing young women born between 1980 and 2000. We tried to understand what these professionals expect from its insertion in the labor market. The results confirm the analysis of the descriptions of the recent literature on Yrs, because the interviewees proved eager for success, professional recognition and attractive remuneration, but also highlight differences and indicate some specifics aspects related to the gender considerations, as expressed by these young woman, which expect to lower their work dedication when they become mothers and wives.